2007
DOI: 10.1111/j.1530-0277.2007.00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences for Ghrelin Levels in Alcohol‐Dependent Patients and Differences Between Alcoholics and Healthy Controls

Abstract: The data suggest gender-dependent ghrelin levels in alcohol-dependent patients. We therefore conclude, that it might be useful to perform statistical analyses gender-specific. With regard to a potential correlation of ghrelin and craving the results seem to depend on gender, duration of the abstinence period and the instrument used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 35 publications
4
30
1
4
Order By: Relevance
“…In particular, Hillemacher et al (2007) reported a significant relationship between ghrelin and OCDS score in an alcoholic subtype (Lesch type 1) characterized by a positive family history of alcoholism. Wurst et al (2007) found a relationship between ghrelin levels and the compulsive subscore of the OCDS scale in female alcoholics. As further evidence of the role of the ghrelin system in AD, a study demonstrated that the SNP rs2232165 of the GHS-R1A gene was associated with heavy alcohol consumption and SNP rs2948694 of the same gene was associated with BMI in heavy alcohol drinkers (Landgren et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In particular, Hillemacher et al (2007) reported a significant relationship between ghrelin and OCDS score in an alcoholic subtype (Lesch type 1) characterized by a positive family history of alcoholism. Wurst et al (2007) found a relationship between ghrelin levels and the compulsive subscore of the OCDS scale in female alcoholics. As further evidence of the role of the ghrelin system in AD, a study demonstrated that the SNP rs2232165 of the GHS-R1A gene was associated with heavy alcohol consumption and SNP rs2948694 of the same gene was associated with BMI in heavy alcohol drinkers (Landgren et al, 2008).…”
Section: Introductionmentioning
confidence: 81%
“…Third, the relatively small sample size did not allow us to perform additional analyses, which should be addressed by future larger studies, i.e. the role of ghrelin according to possible alcoholic subtypes (see: Hillemacher et al, 2007; Leggio et al, 2009c; Leggio, 2010), as well as potential gender differences in the link between ghrelin and alcohol drinking and craving (see: Wurst et al, 2007). Additionally, the trends of ghrelin levels in the abstinent vs. non-abstinent subject, as outlined in the Figure 3 (see in particular T2), might suggest a potential tendency for a homeostatic stabilization of ghrelin levels, although this only remains speculative.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma ghrelin levels have been reported as higher in alcoholics than in controls (Kim et al, 2005;Kraus et al, 2005) and have been positively correlated to the duration of abstinence (Kim et al, 2005) as well as to craving (Addolorato et al, 2006;Hillemacher et al, 2007a;Wurst et al, 2007). Interestingly, in active drinking alcoholics the ghrelin levels were reduced (Addolorato et al, 2006;Badaoui et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has also supported these findings by demonstrating that plasma acyl-ghrelin levels slightly increased during abstinence (0–14 days) (Koopmann et al, 2012). However, there are studies that contradict these findings by showing decreased total ghrelin levels in abstinent alcohol dependents (Wurst et al, 2007; de Timary et al, 2012). These conflicting results may be due to differences in looking at active acyl-ghrelin vs. total ghrelin, gender differences, sample sizes and the time after abstinence.…”
Section: Ghrelinmentioning
confidence: 99%